CoronaVac: A review of efficacy, safety, and immunogenicity of the inactivated vaccine against SARS-CoV-2 - Lairun Jin; Zhuopei Li; Xiaoyin Zhang; Jingxin Li; Fengcai Zhu (Taylor & Francis Group, 2022)
CoronaVac, also known as the Sinovac inactivated SARS-CoV-2 vaccine, has been widely implemented in combating the COVID-19 pandemic. We summarized the results of clinical trials and real-world studies of CoronaVac in this review. The overall efficacy for the prevention of symptomatic COVID-19 (before the emergence of variants of concern) using two doses of 3 μg CoronaVac was 67.7% (95% CI, 35.9% to 83.7%). Effectiveness in preventing hospitalizations, ICU admissions, and deaths was more prominent than that in preventing COVID-19. A third dose inherited the effectiveness against non-variants of concern and increased effectiveness against severe COVID-19 outcomes caused by omicron variants compared to two doses. Most adverse reactions were mild. Few vaccine-related serious adverse reactions have been reported. Moreover, three-dose regimen significantly increased the seroconversion levels of neutralizing antibodies against omicron as compared to two-dose regimen. This review of CoronaVac may provide a scientific basis for optimizing global immunization strategies.